Effects of fabrication parameters on the morphology of porous polysulfone hollow fiber membranes - Mansourizadeh, Amir; Ismail, Ahmad Fauzi (Penerbit UTM Press, 2008)
Porous Polysulfone (PSf) hollow fiber membranes with high porosity were fabricated via a wet spinning phase inversion method, using N-methyl-1-pyrrolidone (NMP, ï€¾99.5%) as solvent, Glycerol as pore-forming additive and water as the coagulation medium. With the addition of the Glycerol, the effect of external coagulation bath composition, dope extrusion rate, additive concentration and post treatment with pure ethanol on the structure of membranes was investigated. The gas permeation method was used to estimate the mean pore size and effective surface porosity of the PSf hollow fiber membranes prepared. The hydrophobicity of the hollow fiber membranes was characterized in terms of contact angle and wetting pressure. Also, mechanical strength of the hollow fibers was tested by collapsing pressure. The fabricated membranes are applicable for membrane gas absorption processes.